User Satisfaction of Accounting Information Systems Using The End User Computing Satisfaction (EUCS) Model: A Systematic Literature Review - Vicky Dzaky Cahaya Putra; Amelia Setiawan (ITB AAS Indonesia Surakarta, 2024)
This study aims to investigate empirically the basis for improving user satisfaction of accounting information systems by using basic theoretical concepts and supporting assessment tables which are the basis for the research topic of User Satisfaction of Accounting Information Systems by using the End User Computing Satisfaction (EUCS) Model for accountants in Indonesian banking companies. This study uses a systematic literature review method by using the Publish or Perish version 8 application as a support for scientific literature collection. The researcher determined that the procedure carried out in collecting the literature of this research was sourced from scientific publications that had indexes on the crossref and google scholar databases. The results of this study found that the EUCS Theory emphasizes five key factors that affect user satisfaction including content, precision, format, usability and timeliness. Each of these dimensions is very important in determining user satisfaction with the accounting information system used.